Fourth Ventricle Tumors: A Review of Series Treated With Microsurgical Technique - Sufianov, Rinat; Pitskhelauri, David; Bykanov, Andrey (Frontiers in Surgery, 2022)
Tumors of the IV ventricle represent 1-5% of all intracranial lesions; they are implicated in 2/3 of the tumors of the ventricular system. According to modern standards, the first treatment stage for this pathology is microsurgical removal. Currently, for the removal of neoplasms of the IV ventricle and brainstem, the median suboccipital approach is widely used, followed by one of the microapproaches. Moreover, with the development of microsurgical techniques, keyhole approaches are now beginning to be utilized. However, surgical treatment of these tumors remains a challenge for neurosurgeons due to the proximity of functionally important anatomical structures (the brainstem, the cerebellum, pathways, vessels, etc.) of the posterior cranial fossa. Therefore, surgery in this area is associated with the possible occurrence of a wide range of postoperative complications. The authors provide a review of series of fourth ventricle tumors treated with microsurgical technique.